Particularidad nacional en una revista continental. Costa Rica y "Repertorio Americano", 1919-1930 - Pakkasvirta, Jussi (1993)
While the Repertorio Americano was a continentalist and hispanic journal, the author seeks to analyze the articles published in the journal on Costa Rica, and attempts to answers the questions: How could two types of community image one of an individual nation, another of a continent at large-coexist?